PERBANDINGAN NILAI BERITA HALAMAN DEPAN PORTAL BERITA RIAUTERKINI.COM DENGAN PORTAL BERITA GORIAU.COM - Juli Efendi; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Indonesia is a democracy country who give chance for mass media to developed tecnology when share the information. Undang-undang No. 40 Tahun 1999 about press said, online media is mass media which based on etic press code.News portal Riauterkini.com and GoRiau.com is online media in Riau which give information according with fact and data based on etic press code in jurnalism. News about Susilo Bambang Yudhoyono came to Riau when finished the problem about burn foresh and smoke in Riau is a interesting news for public especially people in Riau province. The goal in this research is to know about news value compare from Riauterkini.com with GoRiau.com.This research use method descriptive cualitative research with Pan and Kosicki framing analyse tecnique. Data analisis in this research is 10 news from Riauterkini.com and GoRiau.com about Susilo Bambang Yudhoyono arrived to Riau province for finished the problem about burn foresh and smoke. Data collecting tecnique gets through news documentation and interview with editor and reporter.The result of this research showed that news value compare from Riauterkini.com and GoRiau.com is different from news writing. Structur in framing analysis is more completed by GoRiau.com if compare than Riauterkini.com abaout news information. Riauterkini.com more a lot of feature Hardnews (direct news), mean while GoRiau developed news with human interest.com.Keywords : News Values, Framing Analyse, Agenda Setting Theory